NOVEL AND DIRECT MYOFILAMENT-MEDIATED ACTION OF METFORMIN IN THE AGING RIGHT HEART. (11th November 2018) - Bruns, D; Kovacs, E; Jeong, M; Buttrick, P; Walker, L
Abstract: In age-related heart failure as well as other clinical contexts in which aging populations suffer significant morbidity and mortality, right ventricular (RV) function is the strongest predictor of survival. However, despite the clear link between RV dysfunction and mortality, little is known about the impact of age on the RV and there are no direct RV therapies. We hypothesized that activation of AMP-activated protein kinase (AMPK) would be beneficial through direct and novel action on the cardiac contractile apparatus and accordingly, we assessed the impact of age on RV function and the therapeutic potential of AMPK activation by metformin. We used a murine model of pulmonary hypertension-induced RV dysfunction by exposing young (3–4 month) and old ( 20 months) mice to hypobaric hypoxia (HH) (17, 000 feet; PO2 10%) for 4 weeks. Cardiopulmonary morbidity and mortality were significantly accelerated in aged mice exposed to HH, with all mice dying within 4 weeks (compared to 0% of young mice). Advanced age modified the effect of HH on lung and RV weights, indicative of more severe remodeling. At the level of the myofilament, HH exposure increased force production and decreased myofilament cooperativity in isolated cardiomyocytes, suggesting dysregulation of myocyte contractile function. Treatment with metformin significantly improved survival in aged mice (75% alive at 4 weeks), improved cardiopulmonary remodeling, and partially restored myofilament-mediated contractility. These data suggest that activation of AMPK has beneficial effects on contractility in the aging right heart, and will further elucidate therapeutic potential of AMPK activators using pharmacological and genetic approaches.